Transformation, Challenges, and Regulation of Halal Tourism in the 5.0 Era - Lukman Yafi (Demak Universal Journal of Islam and Sharia, 2024)
The halal tourism industry is a growing sector and has recently become a global trend in economic development in many countries. However, halal tourism creates an abnormal situation and brings advantages and disadvantages in various regions in Indonesia. The purpose of this article is to find out the structure of halal tourism development in five regions of Indonesia. This article tries to formulate a model of halal tourism regulation based on community diversity and local wisdom. This research uses legal research techniques with a critical and constructive approach. The results of this study show that the development of halal tourism regulations in various regions shows a positive and dynamic direction, in line with the design of regional tourism policies that need to be further promoted and accelerated. Therefore, in this positive trend and dynamic, the development of halal tourism in the region requires the application of a sustainable halal tourism regulation model based on community diversity and responsive to the wisdom of the local community. The contribution of this article can support the implementation of post-pandemic sustainable halal tourism policies in various local communities.